Role of yoga therapy on lipid profile in patients of hypertension and prehypertension - Mahesh, Nalin Kumar; Kumar, Anil; Bhat, Keshavamurthy Ganapathy; Verma, Niket (International Journal of Advances in Medicine, 2018)
Background: Hypertension and dyslipidemia are one of the most prevalent cardiovascular disorders affecting 20% of world’s population. There is emerging data that yoga therapies may be useful in managing modest elevations in BP. Yoga, specific yogic exercise (Sudarshan kriya) taught as a training protocol under Art of living course (AOL), is especially attractive as a candidate therapy in the management of elevated BP because of its combination of gentle physical activity. Hence, this study was undertaken to compare the effects of SDK on blood lipid levels. Methods: A total of 300 patients of hypertension and prehypertension were taken in the study where control group were given drugs treatment and life style modification and yoga group additionally had undergone yoga training. Lipid levels were estimated in both groups at entry, 06 months and 12 months and analyzed. Results: Lipid levels at entry were same in both while the yoga therapy group showed decrease in TG, LDL and VLDL at six months and 12 months but decrease was not significant. HDL levels showed significant increase in yoga group (P<0.05) at six months which was maintained at 12 months more so in diabetic patients. Conclusions: Yoga therapy has beneficial effect on serum lipid levels and should be included in therapy along with other measures.